Film art an introduction - Bordwell, David; Thompson, Kristin 1950-; Smith, Jeff 1962 December 17- (McGraw-Hill Education, 2020)
"Film Art provides the respected scholarship and analytic tools students need to understand key vocabulary and concepts of film forms, techniques, and history;appreciate a wide variety of classic and contemporary films and the creative choices made by filmmakers to shape the experience of viewers; and analyze films critically and systematically to enrich their understanding and appreciation of any film, in any genre"--